2018
DOI: 10.1167/tvst.7.6.34
|View full text |Cite
|
Sign up to set email alerts
|

Axial Length Shortening After Cataract Surgery: New Approach to Solve the Question

Abstract: PurposeTo check if optical biometry can detect eventual corneal power (Km) and axial length (AL) cataract surgery-related changes that could influence the refractive outcome.MethodsPatients scheduled for sequential bilateral cataract surgery between January and September 2017 were included in the present study. One hundred ninety-six eyes of 98 patients (48 males) were selected. Before surgery of the first eye, patients underwent a complete ophthalmic examination, including IOLMaster biometry; the same evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 29 publications
(38 reference statements)
5
36
2
Order By: Relevance
“…One potential weakness of the present study is that we used the ICP, rather than the GAT, which represents the gold standard for measuring IOP [30]. Regrettably, several corneal parameters, such as biomechanical properties [31,32], CCT [33,34,35], corneal astigmatism [36,37], corneal irregularities [38], and a history of refractive corneal surgery can influence IOP measurements acquired by GAT. Moreover, the purpose of the study was to check the differences between the sitting position and the other positions; importantly, the GAT cannot be used in the ST or supine positions, or if a patient is unable to sit at a slit lamp (e.g., bedridden persons and small children).…”
Section: Discussionmentioning
confidence: 99%
“…One potential weakness of the present study is that we used the ICP, rather than the GAT, which represents the gold standard for measuring IOP [30]. Regrettably, several corneal parameters, such as biomechanical properties [31,32], CCT [33,34,35], corneal astigmatism [36,37], corneal irregularities [38], and a history of refractive corneal surgery can influence IOP measurements acquired by GAT. Moreover, the purpose of the study was to check the differences between the sitting position and the other positions; importantly, the GAT cannot be used in the ST or supine positions, or if a patient is unable to sit at a slit lamp (e.g., bedridden persons and small children).…”
Section: Discussionmentioning
confidence: 99%
“…Another novelty of this study is provided by the classification of the gender populations into AL subgroups, related to the different suggested IOL power formulae, to obtain the best refractive outcomes after cataract surgery. 8,[31][32][33][34][35] Through analysis of these subgroups, we found that CA exhibited a different distribution between males and females. In females, CA was higher when the AL was <21.5 mm, and between 23.5 and 27 mm; lower when the AL was between 21.5 and 23.5 mm; and similar when the AL was >27 mm.…”
Section: Dovepressmentioning
confidence: 95%
“…Changes in AL have been detected after several surgical procedures [ 26 ], but as the authors discussed in their paper, the difference they found in the AL was much more than expected. The reason could be that the preoperative measurements were taken by ultrasound whereas, postoperatively, partial coherence interferometry was used.…”
Section: Discussionmentioning
confidence: 96%